Controlled weakening of model ice: Replicating the mechanical response of summer-warmed sea ice in laboratories and test basins - N. Fuchs; F. von Bock und Polach; P. Buil; S.M. Isay; D. Notz; L. Nupnau; N. Reimer; L. Schoepflin; T. Zorn (Ocean Engineering, 2026)

Corrigendum to “Quality-assurance of heat-flow data: the new structure and evaluation scheme of the IHFC Global Heat Flow Database” [Tectonophysics 863 (2023) / 229976] - Sven Fuchs; Ben Norden; Florian Neumann; Norbert Kaul; Akiko Tanaka; Ilmo T. Kukkonen; Christophe Pascal; Rodolfo Christiansen; Gianluca Gola; Jan Šafanda; Orlando Miguel Espinoza-Ojeda; Ignacio Marzan; et al. (Tectonophysics, 2026)

Experimental study on the interaction of falling films and sprays during cleaning - M. Joppa; R. Schade; T. Hanisch; C. Golla; E. Fuchs; M. Mauermann (Food and Bioproducts Processing, 2026)

Quaternary terrace formation in response to climate, regional uplift and local normal faulting: The Danube terrace staircase of Vienna - B.C. Salcher; S.M. Neuhuber; J.-C. Otto; T. Payer; C. Lüthgens; S. Fuchs; A. Flores-Orozco; J. Nørgaard; S. Grupe; O. Marchhart; A. Wieser; J. Lachner; et al. (Quaternary Science Reviews, 2026)

Implementation of Cognitive (Neuropsychological) Interventions for Older Adults in Clinical or Community Settings: A Scoping Review - Kerryn E. Pike; Lily Li; Sharon L. Naismith; Alex Bahar-Fuchs; Alessandra Lee; Inga Mehrani; Adam Bentvelzen; Nicola T. Lautenschlager; Megan E. O’Connell; Irene Blackberry; Loren Mowszowski (Neuropsychology Review, 2025)
Despite compelling evidence that cognitive interventions for older adults improve cognition, mood, and everyday function, few are implemented in clinical or community practice. This scoping review aims to understand the implementation frameworks and methods used and their contribution to implementation success of cognitive interventions for older adults. We followed the Preferred Reporting Items for Systematic Reviews and Meta-analysis extension for Scoping Reviews (PRISMA-ScR), and searched CINAHL, EMBASE, MEDLINE, and PSYCINFO databases, using terms related to cognitive interventions, implementation, and older adults. This resulted in 5002 studies, of which 29 were included following an iterative process. Most studies reported on implementation of cognitive stimulation for people with dementia. Only four studies used formal implementation frameworks, with three using RE-AIM, and one a process evaluation using complexity theory. The most frequently addressed implementation concepts were Acceptability, Feasibility, and Effectiveness, while Cost, Cost-Effectiveness, and Maintenance were rarely reported. Solutions to common barriers included the importance of good stakeholder relationships and engagement, a manualised intervention flexible enough to adapt to the context, and ensuring facilitators were well-trained, confident, and enthusiastic.

Effectiveness of ozone nanobubble treatments on high biomass cyanobacterial blooms: A mesocosm experiment and field trial - Justin D. Chaffin; David E. Berthold; Eugene C. Braig; Josh D. Fuchs; Rachel S. Gabor; Stephen J. Jacquemin; Haley E. Kuhn; Lillian D. Labus; H. Dail Laughinghouse; Forrest W. Lefler; Heath E. Mash; Heather A. Raymond; et al. (Journal of Environmental Management, 2024)

Long sediment-laden algal turf likely impairs coral recovery on Florida’s coral reefs - A. Duran; K. E. Speare; C. Fuchs; T. C. Adam; L. Palma; M. W. Miller; L. Collado-Vides; A. R. Harborne; D. E. Burkepile (Coral Reefs, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Occurrence and distribution of Grapevine pinot gris virus and other grapevine viruses in German viticultural regions - Noemi Messmer; Patricia Bohnert; Lars Askani; Stefan Schumacher; Ralf T. Voegele; René Fuchs (Journal of Plant Diseases and Protection, 2023)
To determine the occurrence and distribution of prevalent viruses in commercially important vineyards, a survey was carried out in all thirteen wine-growing regions in Germany. Results reveal that the recently emerged Grapevine pinot gris virus (GPGV) was the most abundant virus with a percentage of 18% prevalence, followed by 13% Grapevine fleck virus (GFkV), 9% Grapevine leafroll-associated virus 1 (GLRaV-1), 4% Grapevine fanleaf virus (GFLV), 2% Raspberry ringspot virus (RpRSV), 2% Arabis mosaic virus (ArMV) and 2% Grapevine leafroll-associated virus 3 (GLRaV-3). Distribution of some viruses varies greatly between individual regions, thus regional hotspots or gradients were detected. GPGV for example is mostly found in southeastern Germany, while its incidence decreases to the north along the river Rhine. The findings of this survey provide an overview of the allocation of the most prevalent grapevine viruses in Germany and can support regional virus management and national risk assessment especially GPGV.

GEMAS: Chemical weathering of silicate parent materials revealed by agricultural soil of Europe - Philippe Négrel; Anna Ladenberger; Clemens Reimann; Alecos Demetriades; Manfred Birke; Martiya Sadeghi; S. Albanese; M. Andersson; R. Baritz; M.J. Batista; A. Bel-lan; D. Cicchella; et al. (Chemical Geology, 2023)

Quality-assurance of heat-flow data: The new structure and evaluation scheme of the IHFC Global Heat Flow Database - Sven Fuchs; Ben Norden; Florian Neumann; Norbert Kaul; Akiko Tanaka; Ilmo T. Kukkonen; Christophe Pascal; Rodolfo Christiansen; Gianluca Gola; Jan Šafanda; Orlando Miguel Espinoza-Ojeda; Ignacio Marzan; et al. (Tectonophysics, 2023)

Thermal and behavioural responses of moose to chemical immobilisation from a helicopter - Anne Randi Græsli; Alexandra Thiel; Larissa T. Beumer; Boris Fuchs; Fredrik Stenbacka; Wiebke Neumann; Navinder J. Singh; Göran Ericsson; Jon M. Arnemo; Alina L. Evans (European Journal of Wildlife Research, 2023)
Instrumentation and sample collection for wildlife research and management may require chemical immobilisation of animals, which may entail physiological and behavioural effects on them. It is therefore important to evaluate the immobilisation protocols to reduce the risk of mortality and morbidity of the handled animals and their populations. Using a multi-sensor approach, we assessed the short-term (< 10 days) thermal and behavioural responses of 10 adult female moose ( Alces alces ) equipped with ruminal temperature loggers and GPS collars with accelerometers to helicopter-based chemical immobilisations. We investigated the body temperature ( T b ), movement rates, and resting time before, during, and after recapture. Chemical immobilisations on average increased maximum T b by 0.71 °C during the capture day, and imposed longer travel distances during the capture day and the two following days (3.8 and 1.8 km, respectively), compared to a 10-day reference period before the immobilisation. The probability of resting was 5–6% lower on the capture day and the two following days compared to the reference period, and females with offspring had a higher probability of resting than females without. Maximum T b , movement rate, and resting time returned to pre-capture levels on an individual level 2 h, 3 days, and 3 days after the immobilisation, respectively. Chemical immobilisation of moose from a helicopter increases the energy expenditure deduced through movement and T b rise lasting for hours to days. Ecological and physiological studies aimed at inferring general patterns may encounter bias if including sensor and tracking data from tagged animals without accounting for potential post-capture effects.

Determining seasonal recharge, storage changes, and specific yield using repeat microgravity and water-level measurements in the Mesilla Basin alluvial aquifer, New Mexico, 2016–2018 - Andrew J. Robertson; Jeffrey R. Kennedy; Libby M. Wildermuth; Meghan T. Bell; Erek H. Fuchs; Alex Rinehart; Irene Fernald (Journal of Applied Geophysics, 2023)

Hybrid conferences: opportunities, challenges and ways forward - Eleonora Puccinelli; Daniela Zeppilli; Paris V. Stefanoudis; Annaïg Wittische-Helou; Marjorie Kermorgant; Sandra Fuchs; Lénaïck Menot; Erin E. Easton; Alexandra A-T. Weber (Frontiers in Marine Science, 2022)
Hybrid conferences are in-person events that have an online component. This type of meeting format was rare before the COVID-19 pandemic, but started to become more common recently given the asynchronous global progression of the pandemic, the uneven access to vaccines and different travel regulations among countries that led to a large proportion of participants being unable to attend conferences in person. Here we report the organization of a middle-sized (581 participants: 159 onsite, 422 online) international hybrid conference that took place in France in September 2021. We highlight particular organizational challenges inherent to this relatively new type of meeting format. Furthermore, we surveyed both in-person and online participants to better understand their conference experience and to propose improvements based on the feedback received. Finally, we compare the advantages and disadvantages of three types of conferences (onsite-only, online-only and hybrid) and suggest that hybrid events should be favored in the future because they offer the most flexibility to participants. We conclude by proposing suggestions and ways forward to maximize accessibility and inclusivity of hybrid conferences. Our study brings novel insights on the challenges and opportunities created by hybrid conferences, by reporting not only the organizing committee experience but also by considering the participants’ perspective.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Missense and truncating variants in CHD5 in a dominant neurodevelopmental disorder with intellectual disability, behavioral disturbances, and epilepsy - Ilaria Parenti; Daphné Lehalle; Caroline Nava; Erin Torti; Elsa Leitão; Richard Person; Takeshi Mizuguchi; Naomichi Matsumoto; Mitsuhiro Kato; Kazuyuki Nakamura; Stella A. de Man; Heidi Cope; et al. (Human Genetics, 2021)
Located in the critical 1p36 microdeletion region, the chromodomain helicase DNA-binding protein 5 ( CHD5 ) gene encodes a subunit of the nucleosome remodeling and deacetylation (NuRD) complex required for neuronal development. Pathogenic variants in six of nine chromodomain (CHD) genes cause autosomal dominant neurodevelopmental disorders, while CHD5 -related disorders are still unknown. Thanks to GeneMatcher and international collaborations, we assembled a cohort of 16 unrelated individuals harboring heterozygous CHD5 variants, all identified by exome sequencing. Twelve patients had de novo CHD5 variants, including ten missense and two splice site variants. Three familial cases had nonsense or missense variants segregating with speech delay, learning disabilities, and/or craniosynostosis. One patient carried a frameshift variant of unknown inheritance due to unavailability of the father. The most common clinical features included language deficits (81%), behavioral symptoms (69%), intellectual disability (64%), epilepsy (62%), and motor delay (56%). Epilepsy types were variable, with West syndrome observed in three patients, generalized tonic–clonic seizures in two, and other subtypes observed in one individual each. Our findings suggest that, in line with other CHD-related disorders, heterozygous CHD5 variants are associated with a variable neurodevelopmental syndrome that includes intellectual disability with speech delay, epilepsy, and behavioral problems as main features.

Full Parameterisation Matters for the Best Performance of Crop Models: Inter-comparison of a Simple and a Detailed Maize Model - A. M. Manschadi; J. Eitzinger; M. Breisch; W. Fuchs; T. Neubauer; A. Soltani (International Journal of Plant Production, 2021)
Process-based crop growth models have become indispensable tools for investigating the effects of genetic, management, and environmental factors on crop productivity. One source of uncertainty in crop model predictions is model parameterization, i.e. estimating the values of model input parameters, which is carried out very differently by crop modellers. One simple (SSM-iCrop) and one detailed (APSIM) maize ( Zea mays L.) model were partially or fully parameterized using observed data from a 2-year field experiment conducted in 2016 and 2017 at the UFT (Universitäts- und Forschungszentrum Tulln, BOKU) in Austria. Model initialisation was identical for both models based on field measurements. Partial parameterization (ParLevel_1) was first performed by estimating only those parameters related to crop phenology. Full parameterization (ParLevel_2) was then conducted by estimating parameters related to phenology plus those affecting dry mass production and partitioning, nitrogen uptake, and grain yield formation. With ParLevel_1, both models failed to provide accurate estimation of LAI, dry mass accumulation, nitrogen uptake and grain yield, but the performance of APSIM was generally better than SSM-iCrop. Full parameterization greatly improved the performance of both crop models, but it was more effective for the simple model, so that SSM-iCrop was equally well or even better compared to APSIM. It was concluded that full parameterization is indispensable for improving the accuracy of crop model predictions regardless whether they are simple or detailed. Simple models seem to be more vulnerable to incomplete parameterization, but they better respond to full parameterization. This needs confirmation by further research.

Evaluation of two rapid antigen tests to detect SARS-CoV-2 in a hospital setting - Andreas Osterman; Hanna-Mari Baldauf; Marwa Eletreby; Jochen M. Wettengel; Suliman Q. Afridi; Thimo Fuchs; Elena Holzmann; Anton Maier; Johanna Döring; Natascha Grzimek-Koschewa; Maximilian Muenchhoff; Ulrike Protzer; et al. (Medical Microbiology and Immunology, 2021)
Successful containment strategies for the SARS-CoV-2 pandemic will depend on reliable diagnostic assays. Point-of-care antigen tests (POCT) may provide an alternative to time-consuming PCR tests to rapidly screen for acute infections on site. Here, we evaluated two SARS-CoV-2 antigen tests: the STANDARD™ F COVID-19 Ag FIA (FIA) and the SARS-CoV-2 Rapid Antigen Test (RAT). For diagnostic assessment, we used a large set of PCR-positive and PCR-negative respiratory swabs from asymptomatic and symptomatic patients and health care workers in the setting of two University Hospitals in Munich, Germany, i.e. emergency rooms, patient care units or employee test centers. For FIA, overall clinical sensitivity and specificity were 45.4% ( n = 381) and 97.8% ( n = 360), respectively, and for RAT, 50.3% ( n = 445) and 97.7% ( n = 386), respectively. For primary diagnosis of asymptomatic and symptomatic individuals, diagnostic sensitivities were 60.9% (FIA) ( n = 189) and 64.5% (RAT) ( n = 256). This questions these tests’ utility for the reliable detection of acute SARS-CoV-2-infected individuals, in particular in high-risk settings. We support the proposal that convincing high-quality outcome data on the impact of false-negative and false-positive antigen test results need to be obtained in a POCT setting. Moreover, the efficacy of alternative testing strategies to complement PCR assays must be evaluated by independent laboratories, prior to widespread implementation in national and international test strategies.

Tryptophan depletion predicts lower positive affect in sexual minority men living with HIV who use methamphetamine - Ji-Young Lee; Tiffany R. Glynn; Judith T. Moskowitz; Dietmar Fuchs; Torsten B. Neilands; Samantha E. Dilworth; Daniel J. Feaster; Allan Rodriguez; Adam W. Carrico (Journal of NeuroVirology, 2021)

Ecosystem transpiration and evaporation: Insights from three water flux partitioning methods across FLUXNET sites - Jacob A. Nelson; Oscar Pérez‐Priego; Sha Zhou; Rafael Poyatos; Yao Zhang; Peter D. Blanken; Teresa E. Gimeno; Georg Wohlfahrt; Ankur R. Desai; Beniamino Gioli; Jean‐Marc Limousin; Damien Bonal; et al. (Global Change Biology, 2020)
We apply and compare three widely applicable methods for estimating ecosystem transpiration ( T ) from eddy covariance (EC) data across 251 FLUXNET sites globally. All three methods are based on the coupled water and carbon relationship, but they differ in assumptions and parameterizations. Intercomparison of the three daily T estimates shows high correlation among methods ( R between .89 and .94), but a spread in magnitudes of T /ET (evapotranspiration) from 45% to 77%. When compared at six sites with concurrent EC and sap flow measurements, all three EC‐based T estimates show higher correlation to sap flow‐based T than EC‐based ET. The partitioning methods show expected tendencies of T /ET increasing with dryness (vapor pressure deficit and days since rain) and with leaf area index (LAI). Analysis of 140 sites with high‐quality estimates for at least two continuous years shows that T /ET variability was 1.6 times higher across sites than across years. Spatial variability of T /ET was primarily driven by vegetation and soil characteristics (e.g., crop or grass designation, minimum annual LAI, soil coarse fragment volume) rather than climatic variables such as mean/standard deviation of temperature or precipitation. Overall, T and T /ET patterns are plausible and qualitatively consistent among the different water flux partitioning methods implying a significant advance made for estimating and understanding T globally, while the magnitudes remain uncertain. Our results represent the first extensive EC data‐based estimates of ecosystem T permitting a data‐driven perspective on the role of plants’ water use for global water and carbon cycling in a changing climate.

Calcium intake and colon cancer risk subtypes by tumor molecular characteristics - NaNa Keum; Li Liu; Tsuyoshi Hamada; Zhi Rong Qian; Jonathan A. Nowak; Yin Cao; Annacarolina da Silva; Keisuke Kosumi; Mingyang Song; Daniel Nevo; Molin Wang; Andrew T. Chan; et al. (Cancer Causes & Control, 2019)

Modeling $$\hbox {CO}_2$$-Induced Alterations in Mt. Simon Sandstone via Nanomechanics - Ange-Therese Akono; Pooyan Kabir; Zhuofan Shi; Samantha Fuchs; Theodore T. Tsotsis; Kristian Jessen; Charles J. Werth (Rock Mechanics and Rock Engineering, 2019)

Metabolic versatility of a novel N 2 ‐fixing Alphaproteobacterium isolated from a marine oxygen minimum zone - Clara Martínez‐Pérez; Wiebke Mohr; Anne Schwedt; Julia Dürschlag; Cameron M. Callbeck; Harald Schunck; Julien Dekaezemacker; Caroline R. T. Buckner; Gaute Lavik; Bernhard M. Fuchs; Marcel M. M. Kuypers (Environmental Microbiology, 2018)
Summary The N 2 ‐fixing (diazotrophic) community in marine ecosystems is dominated by non‐cyanobacterial microorganisms. Yet, very little is known about their identity, function and ecological relevance due to a lack of cultured representatives. Here we report a novel heterotrophic diazotroph isolated from the oxygen minimum zone (OMZ) off Peru. The new species belongs to the genus Sagittula ( Rhodobacteraceae , Alphaproteobacteria ) and its capability to fix N 2 was confirmed in laboratory experiments. Genome sequencing revealed that it is a strict heterotroph with a high versatility in substrate utilization and energy acquisition mechanisms. Pathways for sulfide oxidation and nitrite reduction to nitrous oxide are encoded in the genome and might explain the presence throughout the Peruvian OMZ. The genome further indicates that this novel organism could be in direct interaction with other microbes or particles. NanoSIMS analyses were used to compare the metabolic potential of S. castanea with single‐cell activity in situ ; however, N 2 fixation by this diazotroph could not be detected at the isolation site. While the biogeochemical impact of S. castanea is yet to be resolved, its abundance and widespread distribution suggests that its potential to contribute to the marine N input could be significant at a larger geographical scale.

Validation of a KHV antibody enzyme‐linked immunosorbent assay (ELISA) - S M Bergmann; Q Wang; W Zeng; Y Li; Y Wang; M Matras; M Reichert; D Fichtner; M Lenk; T Morin; N J Olesen; H F Skall; et al. (Journal of Fish Diseases, 2017)
Koi herpesvirus ( KHV ) causes KHV disease ( KHVD ). The virus is highly contagious in carp or koi and can induce a high mortality. Latency and, in some cases, a lack of signs presents a challenge for virus detection. Appropriate immunological detection methods for anti‐ KHV antibodies have not yet been fully validated for KHV . Therefore, it was developed and validated an enzyme‐linked immunosorbent assay ( ELISA ) to detect KHV antibodies. The assay was optimized with respect to plates, buffers, antigens and assay conditions. It demonstrated high diagnostic and analytical sensitivity and specificity and was particularly useful at the pond or farm levels. Considering the scale of the carp and koi industry worldwide, this assay represents an important practical tool for the indirect detection of KHV , also in the absence of clinical signs.

Relatedness of wildlife and livestock avian isolates of the nosocomial pathogen Acinetobacter baumannii to lineages spread in hospitals worldwide - Gottfried Wilharm; Evelyn Skiebe; Paul G. Higgins; Marie T. Poppel; Ulrike Blaschke; Sarah Leser; Christine Heider; Magdalena Heindorf; Paul Brauner; Udo Jäckel; Karin Böhland; Christiane Cuny; et al. (Environmental Microbiology, 2017)
Summary The natural habitats and potential reservoirs of the nosocomial pathogen Acinetobacter baumannii are poorly defined. Here, we put forth and tested the hypothesis of avian reservoirs of A . baumannii . We screened tracheal and rectal swab samples from livestock (chicken, geese) and wild birds (white stork nestlings) and isolated A . baumannii from 3% of sampled chicken ( n = 220), 8% of geese ( n = 40) and 25% of white stork nestlings ( n = 661). Virulence of selected avian A . baumannii isolates was comparable to that of clinical isolates in the Galleria mellonella infection model. Whole genome sequencing revealed the close relationship of an antibiotic‐susceptible chicken isolate from Germany with a multidrug‐resistant human clinical isolate from China and additional linkages between livestock isolates and human clinical isolates related to international clonal lineages. Moreover, we identified stork isolates related to human clinical isolates from the United States. Multilocus sequence typing disclosed further kinship between avian and human isolates. Avian isolates do not form a distinct clade within the phylogeny of A . baumannii , instead they diverge into different lineages. Further, we provide evidence that A . baumannii is constantly present in the habitats occupied by storks. Collectively, our study suggests A . baumannii could be a zoonotic organism that may disseminate into livestock.

A prospective study of oral contraceptive use and colorectal adenomas - Brittany M. Charlton; Edward Giovannucci; Charles S. Fuchs; Andrew T. Chan; Jung Eun Lee; Yin Cao; Stacey A. Missmer; Bernard A. Rosner; Susan E. Hankinson; Walter Willett; Kana Wu; Karin B. Michels (Cancer Causes & Control, 2016)

Television watching and colorectal cancer survival in men - Yin Cao; Jeffrey A. Meyerhardt; Andrew T. Chan; Kana Wu; Charles S. Fuchs; Edward L. Giovannucci (Cancer Causes & Control, 2015)

An additional substrate binding site in a bacterial phenylalanine hydroxylase - Judith A. Ronau; Lake N. Paul; Julian E. Fuchs; Isaac R. Corn; Kyle T. Wagner; Klaus R. Liedl; Mahdi M. Abu-Omar; Chittaranjan Das (European Biophysics Journal, 2013)

Prospective cohort studies of bowel movement frequency and laxative use and colorectal cancer incidence in US women and men - Xuehong Zhang; Kana Wu; Eunyoung Cho; Jing Ma; Andrew T. Chan; Xiang Gao; Walter C. Willett; Charles S. Fuchs; Edward L. Giovannucci (Cancer Causes & Control, 2013)

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

A dietary pattern that is associated with C-peptide and risk of colorectal cancer in women - Teresa T. Fung; Frank B. Hu; Matthias Schulze; Michael Pollak; Tianying Wu; Charles S. Fuchs; Edward Giovannucci (Cancer Causes & Control, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Association of the TCF7L2 polymorphism with colorectal cancer and adenoma risk - Aditi Hazra; Charles S. Fuchs; Andrew T. Chan; Edward L. Giovannucci; David J. Hunter (Cancer Causes & Control, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

A Prospective Study of Body Mass Index, Hypertension, and Smoking and the Risk of Renal Cell Carcinoma (United States) - Keith T. Flaherty; Charles S. Fuchs; Graham A. Colditz; Meir J. Stampfer; Frank E. Speizer; Walter C. Willett; Gary C. Curhan (Cancer Causes & Control, 2005)

Size and sequence variability of the Arabis mosaic virus protein 2A - T. Wetzel; M. Fuchs; M. Bobko; G. Krczal (Archives of Virology, 2002)

Abstracts of presentations at the 22nd Congress of the Israeli Phytopathological Society February 12–13,2001 ARO, The Volcani Center, Bet Dagan, Israel - D. Shtienberg; M. Reuveni; N. Shegalov; D. Shegalov; D. Eshel; Ruth Ben-Arie; D. Prusky; Nadia Korolev; J. Katan; Talma Katan; A. Sharon; L. Oren; et al. (Phytoparasitica, 2001)

Flexibility of saccade adaptation in the monkey: different gain states for saccades in the same direction - Shoji Watanabe; Christopher T. Noto; Albert F. Fuchs (Experimental Brain Research, 2000)

A cross-sectional study of workers in the chemical industry with occupational exposure to hexamethylenetetramine - R. Merget; M. Topcu; K. Friese; R. Vormberg; T. Fuchs; M. Raulf-Heimsoth; R. Breitstadt (International Archives of Occupational and Environmental Health, 1999)

Scales of Heterogeneities in the Continental Crust and Upper Mantle - M. Tittgemeyer; F. Wenzel; T. Ryberg; K. Fuchs (Pure and Applied Geophysics, 1999)

Abstracts of papers presented at the 15th conference of the weed science society of Israel - H. Eizenberg; Z. Tanaami; R. Jacobsohn; A. Lalazar; M. Hayut; M. Sibony; A. Tal; B. Rubin; M. Sibony; T. Yossef; D. Plakhine; Y. Kleifeld; et al. (Phytoparasitica, 1999)

Differential effects of 7-OH-DPAT on amphetamine-induced stereotypy and conditioned place preference - T. V. Khroyan; D. A. Baker; R. A. Fuchs; N. Manders; J. L. Neisewander (Psychopharmacology, 1998)

Genetic basis of resistance to sugarcane mosaic virus in European maize germplasm - A. E. Melchinger; L. Kuntze; R. K. Gumber; T. Lübberstedt; E. Fuchs (Theoretical and Applied Genetics, 1998)

Predictive validity of the extinction/reinstatement model of drug craving - Rita A. Fuchs; L. T. L. Tran-Nguyen; Sheila E. Specio; Robert S. Groff; J. L. Neisewander (Psychopharmacology, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Identification and transcriptional analysis of pseudorabies virus UL6 to UL12 genes - J. M. Dijkstra; W. Fuchs; T. C. Mettenleiter; B. G. Klupp (Archives of Virology, 1997)

Introduction and establishment ofApanteles flavipes [Hym.: Braconidae] onDiatraea saccharalis [Lep.: Pyralidae] in texas - T. W. Fuchs; F. R. Huffman; J. W. Smith (BioControl, 1979)